Comparison of Antarctic total ozone behavior in pre-SSW, SSW, and post-SSW years - Yu, Ruixian; Grytsai, Asen; Milinevsky, Gennadi; Evtushevsky, Oleksandr; Yukhymchuk, Yuliia; Zazubyk, Diana; Klekociuk, Andrew (Ukrainian Antarctic Journal, 2025)
Sudden stratospheric warmings (SSWs) are dramatic events characterized by sudden and sharp changes in the distribution of polar stratospheric temperatures, zonal winds, total ozone column, and other atmospheric parameters. SSWs are usual in the winter season in the Northern Hemisphere, but they are rare in the Antarctic stratosphere. Only one major SSW (September 2002) was observed in the southern polar stratosphere over the entire time of observations. In the paper, this event is considered in conjunction with the warmings of 1988 and 2019, which do not correspond to the major SSW definition, but were accompanied by significant temperature and total ozone increases, as well as zonal wind deceleration. The changes in the total ozone distributions over Antarctica are analyzed using Multi-Sensor Reanalysis (MSR-2) data. We have plotted and analyzed the spatial distribution of total ozone anomalies in the SSW years and adjacent years. A significant zonal asymmetry is noted between the Western and Eastern Hemispheres over Antarctica. In the East Antarctic stratosphere, total ozone increases several weeks before the central date of the warming, indicating preconditions for the event. Quasi-periodic oscillations associated with planetary waves were observed over East Antarctica in 1988 and 2002. On the contrary, total ozone over West Antarctica showed no clear features prior to the warming. The warmings have distinct spatial coverage: in particular, the 1988 event did not penetrate the inner region of the stratospheric polar vortex. In the adjacent years, total ozone was predominantly lower than climatological values, and we have concluded that total ozone decrease is most typical for the previous years (1987, 2001, 2018).